Pubertal Hormonal Changes and the Autonomic Nervous System: Potential Role in Pediatric Orthostatic Intolerance - Coupal, Kassandra E.; Heeney, Natalie D.; Hockin, Brooke C. D.; Ronsley, Rebecca; Armstrong, Kathryn; Sanatani, Shubhayan; Claydon, Victoria E. (Frontiers in Neuroscience, 2019)
Puberty is initiated by hormonal changes in the adolescent body that trigger physical and behavioral changes to reach adult maturation. As these changes occur, some adolescents experience concerning pubertal symptoms that are associated with dysfunction of the autonomic nervous system (ANS). Vasovagal syncope (VVS) and Postural Orthostatic Tachycardia Syndrome (POTS) are common disorders of the ANS associated with puberty that are related to orthostatic intolerance and share similar symptoms. Compared to young males, young females have decreased orthostatic tolerance and a higher incidence of VVS and POTS. As puberty is linked to changes in specific sex and non-sex hormones, and hormonal therapy sometimes improves orthostatic symptoms in female VVS patients, it is possible that pubertal hormones play a role in the increased susceptibility of young females to autonomic dysfunction. The purpose of this paper is to review the key hormonal changes associated with female puberty, their effects on the ANS, and their potential role in predisposing some adolescent females to cardiovascular autonomic dysfunctions such as VVS and POTS. Increases in pubertal hormones such as estrogen, thyroid hormones, growth hormone, insulin, and insulin-like growth factor-1 promote vasodilatation and decrease blood volume. This may be exacerbated by higher levels of progesterone, which suppresses catecholamine secretion and sympathetic outflow. Abnormal heart rate increases in POTS patients may be exacerbated by pubertal increases in leptin, insulin, and thyroid hormones acting to increase sympathetic nervous system activity and/or catecholamine levels. Given the coincidental timing of female pubertal hormone surges and adolescent onset of VVS and POTS in young women, coupled with the known roles of these hormones in modulating cardiovascular homeostasis, it is likely that female pubertal hormones play a role in predisposing females to VVS and POTS during puberty. Further research is necessary to confirm the effects of female pubertal hormones on autonomic function, and their role in pubertal autonomic disorders such as VVS and POTS, in order to inform the treatment and management of these debilitating disorders.